2011
DOI: 10.1592/phco.31.7.649
|View full text |Cite
|
Sign up to set email alerts
|

Otoacoustic Emission Screen Results in Critically Ill Neonates Who Received Gentamicin in the First Week of Life

Abstract: Neonates weighing more than 1500 g at birth and whose gentamicin C(max) exceeded 10 μg/ml were at an increased risk for OAE screen failure. Monitoring and maintaining gentamicin C(max) at or below 10 μg/ml may minimize hearing impairment; however, further studies are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…They found a failure rate of 1st TEOAEs among 84 high risk neonates for hearing loss (including treatment by aminoglycosides) of 21.4% vs 9.8% in 448 healthy, failure rate of 2nd TEOAEs was 8.64% vs 1.37% in high risk vs healthy neonates respectively. Cooper et al [20] found 9.0% (40/ 443 neonates) failure rate of TEOAEs in non-VLBW neonates. VellaBrincat et al [21] showed 7% (85/1,233) failure rate in no gentamicin and no vancomycin group while gentamicin but no vancomycin group showed failure rate of 4% (42/949).…”
Section: Discussionmentioning
confidence: 98%
“…They found a failure rate of 1st TEOAEs among 84 high risk neonates for hearing loss (including treatment by aminoglycosides) of 21.4% vs 9.8% in 448 healthy, failure rate of 2nd TEOAEs was 8.64% vs 1.37% in high risk vs healthy neonates respectively. Cooper et al [20] found 9.0% (40/ 443 neonates) failure rate of TEOAEs in non-VLBW neonates. VellaBrincat et al [21] showed 7% (85/1,233) failure rate in no gentamicin and no vancomycin group while gentamicin but no vancomycin group showed failure rate of 4% (42/949).…”
Section: Discussionmentioning
confidence: 98%
“…Even though ureterostomy induces a need for further surgery, it avoids part of the morbidity associated with pyelonephritis (antibiotics side effects, intravenous injection, and hospitalization) and selection of resistant bacteria due to repeated antibiotic pressure [29][30][31][32] .…”
Section: Morbiditymentioning
confidence: 99%
“…Cooper et al 7 examined hearing loss in 528 infants receiving a high doses of gentamicin. Neonates were clustered into two groups, with less than or more than 1500 g birth weight.…”
Section: Ototoxicity Of Gentamicin In Neonatesmentioning
confidence: 99%